The internationalization of South Korea MNC to Brazil - Lee, Salomão Ha Yoon (2021)
In a worldwide view, the globalization force has brought new opportunities to company towards the global expansion. In which, these international businesses are to focus on core competence, strategic alliance, and competitive advantages. And the case studies represent the growth of multinational companies associated with the internationalization strategy, based on the Eclectic Paradigm. This study undertakes the South Korean MNC active in the Brazilian market, which are HT Micron, Hyundai Motor Brazil, Hyundai Heavy Industry, Sae Dong Brazil, and Samsung Electronics. The present study aims to identify the patterns of similarity and differences in entry mode of South Korea MNC, by exploring the motivation for internationalization and reason for selecting the Brazilian market. To accomplish this purpose, the Eclectic Paradigm, also known as OLI Framework, was studied in the literature review, to understand the Motivation-Seeking (Resource, Market, Efficiency and Strategic-Asset-Seeking) of internationalization, consequently the Ownership, Location, and Internalization Advantages. The methodology presents a qualitative approach of primary and secondary data. In particular, the primary data includes interviews from four field perspective: academic, researcher, intermediator, and multinational. On the other hand, the secondary data are to enhance the data collected from the primary data, and CAGE analysis to explore the institutional differences and similarities between both countries. The study concludes that both countries present substantial institutional differences, in cultural aspects, administrative managerial, geographical opposition, and economic development. The Brazilian market is considered an attractive market allowing to be an internationalization driver factor for country with saturated and limited market. The case of South Korean MNC presented, demonstrated a relatively similar results in motivationseeking reasons, entry mode strategy and the OLI advantages.